ARCHIVES AND HISTORICAL DOCUMENTS: RECORDS OF THE EXPANSION OF THE AGRICULTURAL FRONTIER IN CENTRAL BRAZIL (CIPEEX, 2024)
THIS IS ONGOING RESEARCH AND IS RELATED TO A BROADER PROJECT THAT AIMS TO ANALYZE, BASED ON THE THEORETICAL-METHODOLOGICAL ASSUMPTIONS OF ENVIRONMENTAL HISTORY, THE EXPANSION OF THE AGRICULTURAL FRONTIER IN THE CERRADO, USING AS REFERENCES THE RELATIONSHIP BETWEEN HISTORY, ECOLOGY, AND DEVELOPMENT SCIENCE FOR AGRICULTURE. THUS, WE ARE INTERESTED IN ANALYZING THE GOVERNMENTAL, INSTITUTIONAL, AND ACTOR DISCOURSES AND PRACTICES INVOLVED IN THE AGRARIAN €ŒCONQUEST€ OF THE PHYTOPHYSIOGNOMIC SOILS OF BRAZILIAN FIELDS, WITH EMPHASIS ON THE CLOSED FIELDS OF CENTRAL BRAZIL, AS WELL AS THE INCORPORATION OF THIS REGION IN NATIONAL DEVELOPMENT POLICIES. WE ARE ALSO INTERESTED IN IDENTIFYING AND ANALYZING THE RELATIONSHIP BETWEEN THE AGRONOMIC DEVELOPMENT OF THE CERRADO AND THE MOST RECENT HISTORICAL PROCESSES OF ENVIRONMENTAL DEVASTATION IN THE BIOME. THUS, OUR TIME FRAME SOUGHT TO PRIVILEGE THE CONTEXT OF DEVELOPMENTAL POLICIES IN BRAZIL, WITH THE STUDY OF DOCUMENTARY SOURCES PRODUCED BETWEEN THE 1950S AND 1990S, INCLUDING DEBATES ON THE ECOLOGY OF SOILS AND SAVANNAH FIELDS IN CENTRAL BRAZIL. WE THEREFORE LOOK TO THE THEORETICAL ASSUMPTIONS OF ENVIRONMENTAL HISTORY, IN THE SEARCH FOR UNDERSTANDING THE €ŒINVENTION€ OR HISTORICAL CONSTRUCTION OF THE CERRADO IN THE MIDST OF ECOLOGICAL IDEAS AND THE SYMBOLIC STRUGGLE BETWEEN THE DIFFERENT CONCEPTS THAT CULMINATED IN THE HEGEMONIC VISION OF THE BIOME WITH THE GREAT AGRICULTURAL FRONTIER FROM BRAZIL. AND IN THIS SENSE, INTERDISCIPLINARY DIALOGUE WITH OTHER FIELDS OF KNOWLEDGE WILL BE FUNDAMENTAL, IN THE SEARCH TO UNDERSTAND THE ECOLOGICAL, POLITICAL AND ECONOMIC REASONS THAT INVOLVE THE RELATIONSHIP BETWEEN SOCIETY AND THE NATURAL RESOURCES OF THE CERRADO. THUS, IN ADDITION TO ECOLOGY, DIALOGUE WITH AGRONOMY, GEOGRAPHY, ARCHEOLOGY, GEOLOGY, SOIL BIOLOGY AND OTHER AREAS OF KNOWLEDGE WILL BE FUNDAMENTAL, AS IT ALSO ASSOCIATES OTHER HISTORIOGRAPHICAL FIELDS SUCH AS THE HISTORY OF SCIENCE, HISTORY OF AGRICULTURE, AND ENVIRONMENTAL HISTORY. THUS, OUR RESEARCH UNIVERSE SEEKS TO EXPAND THE HISTORIOGRAPHICAL SCOPE TO THE LENSES OF INTERDISCIPLINARITY, SO FUNDAMENTAL TO THE THEORETICAL-METHODOLOGICAL ASSUMPTIONS OF ENVIRONMENTAL HISTORY. OUR INTENTION IS TO ESTABLISH AN ENVIRONMENTAL HISTORY OF THE CERRADO BASED ON THE HISTORICAL PROCESSES OF AGRICULTURAL EXPANSION IN THIS REGION, WHICH IS CURRENTLY THE MAIN PRODUCER OF AGRICULTURAL COMMODITIES IN THE COUNTRY, AND ITS ECONOMIC AND SOCIO-ENVIRONMENTAL EFFECTS. IN THE CASE OF THE WORK PLAN FOR THE SCIENTIFIC INITIATION SCHOLARSHIP, WE AIM TO TRAIN STUDENT RESEARCHERS IN DEALING WITH HISTORICAL DOCUMENTARY SOURCES, ARCHIVES, AND THE COLLECTION AND ANALYSIS OF THESE SOURCES, ASSOCIATED WITH THE THEORETICAL-METHODOLOGICAL ASSUMPTIONS OF ENVIRONMENTAL HISTORY. (FONTE: ARIAL, 11, ESPAAMENTO SIMPLES)
Keywords: Cerrado; Agricultural History; Historical Archives; Documentary Sources